Performance Analysis of a PWM Current Controlled Five Phase Induction Motor Drive for Disturbances and Faulty Condition - Bashudeb Chandra Ghosh; Md. Ershad Ali (Journal of Power Electronics and Devices, 2019)
Multiphase induction motors are recently used in applications like electric vehicles, high power drives with increased degree of freedom and energy conversion systems where reliability is a great concern. Recently, availability of fast switching devices and controlling digital processors has focused interest on the use of multiphase induction motor drives. In this paper, a five phase induction motor has been considered for study the drive performance. The mutually perpendicular stationary reference frame model of the motor is considered for simulation study. For field orientation control law implementation, the synchronously rotating frame current components are used and with these the slip speed is calculated. The reference torque component of current is generated by processing the speed error through a conventional PI controller. The current regulated PWM control is implemented through a hysteresis controller for switching to proper dc voltage. The drive performance was evaluated by writing C++ codes in code block environment. Simulation results are presented to describe the drive performance which show the very fast response of the drive system during transient conditions. The drive system speed is found to immune due to sudden load torque changes and phase fault conditions thus justifying the effectiveness of the drive system.